2021
DOI: 10.1002/anie.202105851
|View full text |Cite
|
Sign up to set email alerts
|

Ethane‐Based Catalytic Process for Vinyl Chloride Manufacture

Abstract: The use of ethane as ap latform molecule for the manufacture of polyvinyl chloride (PVC) is al ongstanding challenge,whichwould allowtoreduce the raw material costs and CO 2 emissions to produce this plastic.Herein, we discover that rare earth oxychlorides catalyzeinaselective (up to 90 %) and stable (> 50 ho ns tream) manner the reaction of ethane and molecular chlorine into 1,2-dichloroethane,w hich, upon established cracking, will translate into an order of magnitude higher vinyl chloride productivity compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The direct hydrochlorination of coal-derived acetylene leads to vinyl chloride monomer (VCM) using toxic HgCl2 catalysts [7][8][9] . The ethylene-based balanced process (EBP) integrates the direct chlorination/oxychlorination of oil-derived ethylene and pyrolysis of ethylene dichloride (EDC) to produce VCM and has been widely adopted by VCM producers since the mid-1950s, accounting for nearly all capacities worldwide [10][11][12] . Although these industrial processes are suboptimal due to the use of relatively expensive and high carbon footprint feedstocks 12,13 , a new reaction route that can rival the existing ones in terms of cost and energy efficiencies is still underdeveloped.…”
Section: Mainmentioning
confidence: 99%
See 2 more Smart Citations
“…The direct hydrochlorination of coal-derived acetylene leads to vinyl chloride monomer (VCM) using toxic HgCl2 catalysts [7][8][9] . The ethylene-based balanced process (EBP) integrates the direct chlorination/oxychlorination of oil-derived ethylene and pyrolysis of ethylene dichloride (EDC) to produce VCM and has been widely adopted by VCM producers since the mid-1950s, accounting for nearly all capacities worldwide [10][11][12] . Although these industrial processes are suboptimal due to the use of relatively expensive and high carbon footprint feedstocks 12,13 , a new reaction route that can rival the existing ones in terms of cost and energy efficiencies is still underdeveloped.…”
Section: Mainmentioning
confidence: 99%
“…The ethylene-based balanced process (EBP) integrates the direct chlorination/oxychlorination of oil-derived ethylene and pyrolysis of ethylene dichloride (EDC) to produce VCM and has been widely adopted by VCM producers since the mid-1950s, accounting for nearly all capacities worldwide [10][11][12] . Although these industrial processes are suboptimal due to the use of relatively expensive and high carbon footprint feedstocks 12,13 , a new reaction route that can rival the existing ones in terms of cost and energy efficiencies is still underdeveloped. Very recently, it has been demonstrated that using natural gas-derived ethane as the feedstock, VCM could be made at a cheaper cost and with less CO2 emissions 12,14 .…”
Section: Mainmentioning
confidence: 99%
See 1 more Smart Citation
“…The direct hydrochlorination of coal-derived acetylene leads to vinyl chloride monomer (VCM) using toxic HgCl2 catalysts [4][5][6] . The ethylene-based balanced process (EBP) integrates the direct chlorination/oxychlorination of oil-derived ethylene and pyrolysis of ethylene dichloride (EDC) to produce VCM and has been widely adopted by VCM producers since the mid-1950s, accounting for nearly all capacities worldwide [7][8][9] .…”
Section: Mainmentioning
confidence: 99%
“…Although these industrial processes are suboptimal due to the use of relatively expensive and high carbon footprint feedstocks 9,10 , a new reaction route that can rival the existing ones in terms of cost and environmental impact is still underdeveloped.…”
Section: Mainmentioning
confidence: 99%